Contested ‘respectability’: gender and labour in the life stories of Tanzanian women and men in the hospitality industry - Fischer, Gundula (Informa UK Limited, 2018)
Although ‘disrespectability’ has been discerned as an important discourse that accompanies Tanzanian women’s engagement in hospitality jobs, it remains unclear how they counter this devaluation and whether their male co-workers are affected as well. Using a life-story methodology with a sample of 20 male and female employees, this study shows how men and women are unevenly hit by the assignment of ‘shame’ and how they resist. Better pay and more professional training could improve workers’ standing, but might also trigger new processes of closure detrimental to gender equity.